B-cell lymphopoiesis is influenced by cathepsin L - Badano, Maria Noel (2013)
Cathepsin L (CTSL) is a ubiquitously expressed lysosomal cysteine peptidase with diverse and highly specific functions. The involvement of CTSL in thymic CD4+ T-cell positive selection has been well documented. Using CTSLnkt/nkt mice that lack CTSL activity, we have previously demonstrated that the absence of CTSL activity affects the homeostasis of the T-cell pool by decreasing CD4+ cell thymic production and increasing CD8+ thymocyte production. Herein we investigated the influence of CTSL activity on the homeostasis of peripheral B-cell populations and bone marrow (BM) B-cell maturation. B-cell numbers were increased in lymph nodes (LN), spleen and blood from CTSLnkt/nkt mice. Increases in splenic B-cell numbers were restricted to transitional T1 and T2 cells and to the marginal zone (MZ) cell subpopulation. No alterations in the proliferative or apoptosis levels were detected in peripheral B-cell populations from CTSLnkt/nkt mice. In the BM, the percentage and the absolute number of pre-pro-B, pro-B, pre-B, immature and mature B cells were not altered. However, and experiments showed that BM B-cell production was markedly increased in CTSLnkt/nkt mice. Besides, BM B-cell emigration to the spleen was increased in CTSLnkt/nkt mice. Colony-forming unit pre-B (CFU pre-B) assays in the presence of BM stromal cells (SC) and reciprocal BM chimeras revealed that both BM B-cell precursors and SC would contribute to sustain the increased B-cell hematopoiesis in CTSLnkt/nkt mice. Overall, our data clearly demonstrate that CTSL negatively regulates BM B-cell production and output therefore influencing the homeostasis of peripheral B cells.